2011
DOI: 10.4061/2011/891259
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Hemodialysis Catheter Dysfunction Defined According to National Kidney Foundation Guidelines As Blood Flow <300 mL/min

Abstract: Blood flow rate (BFR) <300 mL/min commonly is used to define hemodialysis catheter dysfunction and the need for interventions to prevent complications. The objective of this study was to describe patterns of unplanned BFR <300 mL/min during catheter hemodialysis using data from DaVita dialysis facilities and the United States Renal Data System. Patients were included if they received at least eight weeks of hemodialysis exclusively through a catheter between 08/04 and 12/06, and catheter hemodialysis was the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 6 publications
1
6
0
3
Order By: Relevance
“…Our findings that patient variables are associated with both predicting the time to first TPA use (i.e., increasing body mass index and black race) and its success after TPA administration (i.e., decreasing body mass index and having diabetes) are consistent with the findings of other studies (13)(14)(15). While the biologic mechanisms for these associations have not yet been studied, prior clinical studies have found that being male (13), being black (vs. white) (13) and having diabetes (14,15) were associated with a higher risk of catheter malfunction and previous catheter use (14) was associated with decreased time to catheter removal.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings that patient variables are associated with both predicting the time to first TPA use (i.e., increasing body mass index and black race) and its success after TPA administration (i.e., decreasing body mass index and having diabetes) are consistent with the findings of other studies (13)(14)(15). While the biologic mechanisms for these associations have not yet been studied, prior clinical studies have found that being male (13), being black (vs. white) (13) and having diabetes (14,15) were associated with a higher risk of catheter malfunction and previous catheter use (14) was associated with decreased time to catheter removal.…”
Section: Discussionsupporting
confidence: 92%
“…While CVC location has been identified as a risk factor for malfunction, this study examined non-tunnelled catheters only [ 24 ]. An observational cohort study of 3,364 incident and prevalent HD patients with a CVC in the United States reported the risk of CVC malfunction (blood flow <300 mL/min) was lower for males and black race (compared with white) and higher if CVC was not the first access modality [ 25 ]. Male patients in our study were also at decreased risk but, possibly due to small numbers, we saw no significant effect of first CVC ever or ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“…Catheter dysfunction is defined by the KDOQI as the inability to reach a BFR of 300 mL/min within the first hour of dialysis; whereas the most serious causes of catheter dysfunction are loss of blood flow due to sheathing and clotting, dysfunction may also be caused by bends, kinks, holes, or cracks in the tubing (4, 13). Despite optimal implantation techniques, TDCs tend to lose effective blood flow with time due to fibrin sheath formation and the eventual development of thromboses within the sheath, catheter, or the vein.…”
Section: Discussionmentioning
confidence: 99%